2021
DOI: 10.18203/2349-3933.ijam20212866
|View full text |Cite
|
Sign up to set email alerts
|

Virological failure among HIV infected individuals on antiretroviral therapy in Pune, India: a cross-sectional study

Abstract: Background: It is important to identify and manage determinants of virological failure among HIV infected individuals on treatment for achieving viral suppression. This study aimed to identify proportion and factors associated with virological failure among HIV infected individuals receiving first line antiretroviral therapy (ART).Methods: A total of 2670 adult HIV infected individuals attending ART centre at ICMR-National AIDS Research Institute, between January 2005 and June 2019 and having their recent vira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
(48 reference statements)
0
1
1
Order By: Relevance
“…Although the rate of VTF was higher among PLHIV who stated ART with CD4 <200 cells/mL (11.6% (95% CI: 8.1%, 15.1%)) compared to those who started ART with CD4 > = 200 cells/ mL (8.1% (95% CI:6.4%, 9.9%)), this difference was not statistically significant, p = 0.062. The failure rate of 3.7% among adults in this study was inconsistent with previous findings from studies conducted among adults in Ethiopia, Uganda, India, and Kenya [13,14,[22][23][24][25][26][27], where rates of VTF among adults ranged from about 10% to as high as 34%. Many of these studies however, used the definition of two consecutive VL >1000 copies/ml 3 3 months apart, without the condition of adherence counseling, somewhat different to the definition used in our study.…”
Section: Plos Global Public Healthcontrasting
confidence: 99%
“…Although the rate of VTF was higher among PLHIV who stated ART with CD4 <200 cells/mL (11.6% (95% CI: 8.1%, 15.1%)) compared to those who started ART with CD4 > = 200 cells/ mL (8.1% (95% CI:6.4%, 9.9%)), this difference was not statistically significant, p = 0.062. The failure rate of 3.7% among adults in this study was inconsistent with previous findings from studies conducted among adults in Ethiopia, Uganda, India, and Kenya [13,14,[22][23][24][25][26][27], where rates of VTF among adults ranged from about 10% to as high as 34%. Many of these studies however, used the definition of two consecutive VL >1000 copies/ml 3 3 months apart, without the condition of adherence counseling, somewhat different to the definition used in our study.…”
Section: Plos Global Public Healthcontrasting
confidence: 99%
“…Nonetheless, Amaewhule et al (2021) reported a higher prevalence (41.1%) of MetS among apparently healthy individuals. This relatively high prevalence may be due to an increase in the adoption of Western (Ayodele et al, 2012;Bosho et al, 2018;Kiama et al, 2018, Shidhaye et al, 2023Muhammad et al, 2017). The variation in the prevalence of MetS among PLWHIV may be due to various criteria used, sample size and also the methodology of the study.…”
Section: Discussionmentioning
confidence: 99%